Family Support with Quality of Life in the Elderly - Dinda Surya; Laili Alfita (Mahesa Research Center, 2025)
This study aims to identify family support with the quality of life of the elderly. In Indonesia, people generally live at home with their families, so the family as one source of social support gives an important meaning to the lives of the elderly, family support is the most influential factor in the quality of life of the elderly, compared to other factors. This is because family support can increase self-confidence in the elderly and motivate them elderly in live their lives. The elderly are in the last phase of life and will experience decline resulting in muscle weakness, degenerative diseases, anxiety, and depression. The elderly need support from others. Family support is an important element to motivate the elderly, increase self-confidence, and help the elderly in meeting their needs and facing their problems. High family support will improve the quality of life of the elderly. This study uses a quantitative approach. The data collection tool in this study uses a Likert scale model, through a scale of family support and quality of life. Data analysis used Person Product Moment through SPSS Version 23. Based on 11 articles analyzed, it shows that family support affects the quality of life of the elderly because family support has a positive impact on the quality of life.